Case Report: Neuroendocrine Tumor With Cardiac Metastasis - Kinney, Rachel E.; Decker, Robert; Sundlof, Deborah; Rizvi, Muhammad A.; Schadler, Kelly (Frontiers in Cardiovascular Medicine, 2020)
Neuroendocrine tumors (NETs) are a heterogeneous group of neoplasms that arise from cells throughout the neuroendocrine system, most commonly arising from the gastrointestinal (GI) tract, lungs and bronchi. Myocardial carcinoid metastasis is rare with an incidence among metastatic carcinoid patients of 4% and in general are asymptomatic and detected incidentally. Infiltrative myocardial metastasis secondary to carcinoid tumor is exceedingly rare with only single-digit cases reported in the literature. We report the case of a 65-year-old female with a newly diagnosed ileal neuroendocrine tumor as well as heart failure due to infiltrative myocardial metastasis.